Pengaruh Pendekatan Keterampilan Proses Sains Terhadap Hasil Belajar Peserta Didik Kelas VII SMP Negeri 2 Wonomulyo Pada Mata Pelajaran IPA - Dini, Dwi Rahayu; Nurhayati B, Nurhayati B; Syamsiah, Syamsiah (Biology Teaching and Learning, 2021)
Abstract. This study is the quasy experiment research that aimed to know the influence of Science Process Skills Approach to the Study Results of the Student Class VII SMPN 2 Wonomulyo in science subjects in the study of life organization systems.The independent variable in this study is the application of the science process skills approach and eksposotori, while the dependent variable is the learning outcomes of students on the material of life organization systems. The population in this study were all students of class VII SMP Negeri 2 Wonomulyo as many as 6 classes, while the sample was class VII C as the experimental class and class VII B as the control class. In the experimental class, The experimental class was given treatment that was taught using a science process skills approach with 23 students and the control class using an expository approach with 23 students. The research data were obtained by giving a learning outcome test on the material of life organization systems in the form of a pretest and posttest. The data analysis technique is covariate analysis (Anacova). Based on the results of inferential statistical analysis, it was found that P = 0.001 was smaller than Î± = 0.05. It can be concluded that the application of the science process skills approach (Science Process Skills) has a significant effect on the learning outcomes of Class VII Students of SMP Negeri 2 Wonomulyo in science subjects in the study of life organization systems.Keywords:Â  science process skills approach, learning outcome, life organizationÂ  systems